1974
DOI: 10.1128/jb.119.2.443-449.1974
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cell Division Regulation: Characterization of the dnaH Locus of Escherichia coli

Abstract: The dnaH locus is the fourth gene to be identified as required for deoxyribonucleic acid polymerization in Escherichia coli. A temperature-sensitive mutant defective in this gene exhibited an abrupt decrease in rate of deoxyribonucleic acid synthesis when shifted to 42 C. The locus mapped in the proC-purE region of the chromosome by conjugation and was co-transducible with purE. dnaH+ is carried on the F',8 episome and is dominant over the dnaHmutation.Mutations which cause temperature sensitivity of deoxyribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 40 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…The oriC+, dnaA+ dnaX(Ts) strain also stopped growth at 39°C after a 20‐fold absorbance increase over about 4 h (data not shown). At the more restrictive 42°C, a dnaX(Ts) mutant stopped DNA synthesis quickly with an average 17% increment and growth ceased after a fourfold mass increase over a 2 h period (Filip et al ., 1974).…”
Section: Resultsmentioning
confidence: 99%
“…The oriC+, dnaA+ dnaX(Ts) strain also stopped growth at 39°C after a 20‐fold absorbance increase over about 4 h (data not shown). At the more restrictive 42°C, a dnaX(Ts) mutant stopped DNA synthesis quickly with an average 17% increment and growth ceased after a fourfold mass increase over a 2 h period (Filip et al ., 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Position ofdnaZ on the E. coli map. Earlier mapping by P1 demonstrated that dnaZ is cotransducible with purE but did not determine the sequence of dnaZ with respect to other markers in this region (10). To determine this sequence, phage P1 was grown on strain AX727-(proC+ tsx+ dnaZts purE+) and used to transduce a proC tsx dnaZ + purE recipient (X156) to purE+ and proC+ at 300C.…”
Section: Resultsmentioning
confidence: 99%
“…The Escherichia coli dnaZ gene is one of the four known genes that code for products necessary for deoxyribonucleic acid (DNA) polymerization (10). In addition to participating in E. coli chromosome replication, the dnaZ product also is required for growth of phages M13, OX174, and A, but not for T7 or T4 growth (30,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2A), although not all of the cells were stained at the same intensity with ReAsH due to differences in permeabilization among individual cells. Furthermore, gp8-CCPGCC localization determined in a dnaXts strain, where the temperature sensitivity of the E. coli DNA polymerase III DnaX subunit results in a fast-stop replication elongation block at the non-permissive temperature (Filip et al, 1974), showed no localization at the non-permissive temperature while foci formed at the permissive temperature, indicating that: (i) focus formation was dependent on an active replisome ( Fig. 2A); and (ii) the formation of foci reflected an interaction with a component recruited to the replisome during replication elongation.…”
Section: Gp8 Colocalizes With the E Coli Replisomementioning
confidence: 99%